A low-complexity UWB RF receiver based on a novel low noise amplifier. Issue 8 (August 2015) - Wu, Zhao-Hui; Zhao, Ming-Jian; Wang, Kun; Li, Bin
Abstract A novel low-complexity ultra-wideband UWB receiver is proposed for short-range wireless transmission communications without considering multipath effect. The receiver chip uses a low-complexity UWB non-coherent receiving system solution with the core module composed of squarer and low-pass filter. By introducing asymmetric gate series inductance and RCL parallel negative feedback loop into the two-stage push–pull amplifier, the low-noise amplification and input impedance matching at ultra-wide bandwidth were achieved. With only two inductors and self-biased function, the chip area and power consumption can be saved largely. The proposed UWB receiver chip was fabricated in a 0.18 μm RF CMOS technology. Experimental results show that it can achieve a bandwidth of 3–5 GHz, maximum receiving symbol rate of 250 Mbps, receiving sensitivity of −80 dBm and power consumption of 36 mW, providing a low-complexity and high-speed physical implementation of the short-range high-speed wireless interconnection between electronic devices in the future.